The Role of Organizational Commitment Mediating Organizational Climate with Turnover Intention - Ni Made Dwi Puspitawati; Ni Putu Cempaka Dharmadewi Atmaja (AIBPM Publisher, 2019)
The present study attempts to determine the role of organizational commitment mediating organizational climate with turnover intention in Pizza Hut Denpasar, Bali. A company has to concern about turnover intention because it can create instability and uncertainty about employee conditions, as well as increased recruitment cost. Therefore a company is required to be able to retain employees by understanding things that are able to make employees loyal to the company. This study was conducted with a sample of 55 employees in Pizza Hut Denpasar Bali using the questionnaires with Likert Scale to conclude result that found. This study found that organizational climate has a positive and significant effect on organizational commitment, organizational climate has a negative and significant effect on turnover intention, organizational commitment has a negative and significant effect on turnover intention, and organizational commitment partially mediating organizational climate on turnover intention. Employees will have a high commitment to the company if a good organizational climate is created. A high commitment can reduce intention to leave. Future studies might be more do research about turnover intention from different antecedents. Managers need to develop strategic human resources practice to recruit some potential employees and keep spirit for decresing turnover rate.